Los costos y su incidencia en la rentabilidad de los embutidos elaborados en la Unidad de Producción del Colegio Fiscal Técnico Agropecuario “Balzar” - Zambrano Ruíz, Mélida Virginia (2013)
The objective of this Thesis is to determine the production costs and its impact on the profitability of the sausages produced in the Production Unit Agricultural Technical College "Balzar", to see if the company recovers its costs of production in developing sausages. For this purpose, we apply the methodology of the survey of students and teachers in charge of the control and direction of the Plant Production Unit, through the selection of a random sample analysis conducted after the results were obtained were visualized with the help of statistical graphs and pie, with whose performances proved the research hypothesis in the sense that the cost of production of processed meat products in the Production Unit of the Agricultural Technical College "Balzar" is superior the sales price. By accounting procedure was applied baseline status, general ledger, general ledger sheet, trial balance, statement of cost of goods sold, income statement, breakeven chart and cost sheet, the company detected occupies only 4 hours per week of 40 hours in the same period of time, so you have a net loss of over 50% of their income, meaning that for every dollar invested in the production of sausages, you get $ 0,67 $ 0.33 income and losses represent the campus. Thus arose a proposal to increase the production volume of 3,981 kg to 13,200 kg of sausages, for a net profit equal to 20% on production costs and get a balance point at 6,200 kg, of, that the proposal will be profitable product development in the Production Unit.